RETRACTED: Reduction of additional pressure from ground construction on the subway escalator tunnel - Sokornov A.A.; Konkov A.N.; Konstantinov V.D. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001